Government debt and inflation: A cross-country investigation of the fiscal theory of the price level - Philipp Weber; Lars P. Feld (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2025)
In the early 2020s sharp surge of inflation, unprecedentedly high levels of government debt and deficits fueled attention for the Fiscal Theory of the Price Level (FTPL). This theoretical framework for fiscally induced inflation is well-known and controversially discussed. However, empirical tests are scarce. This paper aims at testing the FTPL empirically by applying a tractable functional form of the intertemporal budget function to a wide range of crises in OECD countries between the years 1980 and 2023. The results imply that between 35 and 40 percent of excess government deficits and spending in times of crises are not financed by orthodox fiscal policy alternatives but instead result in higher prices. This provides empirical evidence for non-Ricardian fiscal policies in times of crises and strengthens the arguments of the FTPL.
Keywords: E31; E62; H62; H63; 330; Fiscal Theory of the Price Level; inflation; fiscal policy; government debt